Calculus late transcendentals - Anton, Howard; Bivens, Irl; Davis, Stephen 1952- (John Wiley & Sons Singapore, 2013)
The new edition of Calculus continues to bring together the best of both new and traditional curricula in an effort to meet the needs of even more instructors teaching calculus. The author team's extensive experience teaching from both traditional and innovative books and their expertise in developing innovative problems put them in an unique position to make this new curriculum meaningful for those going into mathematics and those going into the sciences and engineering. This new text exhibits the same strengths from earlier editions including an emphasis on modeling and a flexible approach to technology.